Variable Presentation of the CYBB Mutation in One Family, Approach to Management, and a Review of the Literature - Tatyana Gavrilova; Ari Zelig; Diana H. Lee (Case Reports in Medicine)
Chronic granulomatous disease (CGD) is a primary immunodeficiency disorder marked by abnormal phagocytic function. CGD affects primarily neutrophils and manifests as an early predisposition to severe life-threatening infections. Additionally, patients with CGD are predisposed to unique autoimmune manifestations. While generally spared from infectious complications, heterozygous carriers of the abnormal genes implicated in CGD pathogenesis can still present with autoimmune disorders. A mutation in the CYBB gene is the only X-linked variant of this disease. This article describes a family with the CYBB mutation, its heterogenous presentation, and reviews the literature discussing disease management.